PENGARUH KOMPLEKSITAS TUGAS, INDEPENDENSI, DAN INTEGRITAS AUDITOR TERHADAP KUALITAS AUDIT (Studi Kasus Pada Kantor Akuntan Publik di Kota Semarang) - Budi Alamsyah, 14.05.52.0302; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2019)
Audit quality is the quality of the auditor’swork that is displayed with reliable audit reports. This study aims tomeasure and evalute auditquality with integrity as a moderating variable. The population in this study were all auditors woking in the Public Accounting Firm in Central Java. Sampling was done by using convenience sampling and obtained a sample of 73 respondents. Primary data collection methods are carried out through a survey method using a questionnnare. Theresult of this study indicate that the complexity of the task does not affect audit quality. Independence has a positive effect on audit quality, and Integrity Auditors do not moderate the influence of task complexity and integrity to moderate the influence on audit quality.